Optimization Of Used Cooking Oil Into Biodiesel With Sulfated Zirconia Zeolit Catalyst - Paramita Dwi Sukmawati (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Used cooking oil is oil that come from oil frying foodstuffs.  The difference of used cooking oil with new vegetable oil lies in the composition of new saturated fatty acids and unsaturated. Used cooking oil has saturated fatty acid that is greater than new vegetable oil. As a result Used cooking oil is very dangerous when consumed and when discharged into the environment and will pollute the around environment. Therefore Used cooking oil is suitable to be used for biodiesel feedstock. Utilization of Used cooking oil as raw material for biodiesel is one of the ways to reduce waste that produce economic value and creating an alternative fuel for diesel fuel substitute. Used cooking oil can be processed into biodiesel by transesterification with methanol using zeolite sulfated zirconia catalyst. Used cooking oil containing free fatty acids of 1,64% and a density of 0,911 g / ml Transesterification of Used cooking oil with sulfated zirconia zeolit catalyst was conducted in a batch reactor with maximum volume of 1000 mL equipped with a heater, thermometer, stirrer, and tap of the sample taker. Variables which were studied in this research include the ratio of methanol to oil (1:4, 1:6, 1:9, 1:12), reaction temperature (100OC, 110OC, 120OC ), and concentration of catalyst (0,5%, 1%, 2%).  Condition process that was optimum was achieved at the ratio of oil to methanol 1:6, 2% catalyst concentration, reaction temperature of 120oC,  and reaction time for 120 minutes with a conversion of 71.62%.